Pyruvate kinase M2 interacts with mammalian sterile 20-like kinase 1 and inhibits tamoxifen-induced apoptosis in human breast cancer cells. Issue 4 (April 2017) - Ji, Feihu; Guo, Bianqin; Wang, Nian; Zhong, Changli; Huang, Liyuan; Huang, Yunxiu; Wei, Lan; Su, Min; Jiang, Yulin; Jin, Qianni; Liu, Yifeng; Zhang, Zhiqian; et al.
Tamoxifen has been reported to be associated with antagonism of estrogen-mediated cell growth signaling and activation of estrogen receptor–independent apoptosis events. It has been demonstrated that mammalian sterile 20-like kinase 1 is a direct target of Caspases to amplify the apoptotic signaling pathway. Here, we presented that breast cancer MCF-7 and SKBR3 cells under treatment with 4-hydroxytamoxifen displayed decreased level of pyruvate kinase M2. Western blot results also showed that 4-hydroxytamoxifen induced the activity of pro-apoptotic protein Caspase-3 in MCF-7 and SKBR3 cells, as evidenced by the cleavage of mammalian sterile 20-like kinase 1 substrate in a dose-dependent manner. Co-immunoprecipitation and immunofluorescence experiments were performed to clarify the relationship between pyruvate kinase M2 and mammalian sterile 20-like kinase 1. The results indicated that mammalian sterile 20-like kinase 1 was associated with pyruvate kinase M2 in cultured mammalian cells, and the interaction between mammalian sterile 20-like kinase 1 and pyruvate kinase M2 was decreased in response to 4-hydroxytamoxifen treatment. In addition, knockdown of pyruvate kinase M2 upregulated the level of cleaved Caspase-3 and subsequently facilitated the nuclear translocation of mammalian sterile 20-like kinase 1. Our data further supplemented the extensive functions of pyruvate kinase M2 in mediating breast cancer cell viability by substantially abating the mammalian sterile 20-like kinase 1–mediated apoptosis. In summary, our results identified that mammalian sterile 20-like kinase 1 is a novel downstream target of pyruvate kinase M2, and knockdown of pyruvate kinase M2 contributes apoptosis via promoting nuclear translocation of mammalian sterile 20-like kinase 1 by enhancing Caspase-3-dependent cleavage.